Moving beyond intermediation: how intermediary organizations shape collaboration dynamics in entrepreneurial ecosystems - Hernández Chea, R.; Mahdad, M.; Minh, Thai Thi; Hjortso, C. N. (Elsevier, 2021)
Recently, increasing attention has been paid to entrepreneurial ecosystems and the process of their formation and function. Researchers have noted the important role that intermediary organizations such as incubators play in connecting various actors within ecosystems. Yet our understanding of this role is limited to a few empirical insights. Using resource dependence and embeddedness as theoretical lenses, the present research examines the role of incubators in entrepreneurial ecosystem formation and function, and analyzes how intermediation activities shape collaboration patterns embedded within entrepreneurial ecosystems. Our findings are based on an empirical investigation of two entrepreneurial ecosystems, one in Kenya and one in Uganda. Our analysis of 38 semi-structured interviews with entrepreneurial actors in these ecosystems reveals the underlying structural, operational, and relational conditions that influence the actors’ interaction with each other. We propose three collaboration patterns that emerge among actors in entrepreneurial ecosystems under these conditions: one-sided dependency-based, joint dependency-based, and mutual dependency-based collaborations. We discuss these patterns in detail and identify the circumstances in which each is most likely to occur. This empirical setting clearly shows that beyond their primary roles of providing space, network, and advice to entrepreneurs, intermediary organizations in entrepreneurial ecosystems play a significant role in orchestrating collaborations. Finally, we reflect on the limitations of this study and offer implications for future research.